2018
DOI: 10.1007/s10554-018-1351-z
|View full text |Cite|
|
Sign up to set email alerts
|

Paclitaxel-coated balloon treatment for functionally nonsignificant residual coronary lesions after balloon angioplasty

Abstract: There is limited data on the efficacy of paclitaxel-coated balloon (PCB) compared to stents for de novo coronary lesions. The purpose of this study was to compare the efficacy of PCB treatment with stent implantation for de novo coronary lesions after successful plain old balloon angioplasty (POBA) guided by fractional flow reserve (FFR). In 200 patients scheduled for elective percutaneous coronary intervention (PCI) for de novo lesions, FFR was measured after POBA (POBA-FFR). If POBA-FFR was ≥ 0.75, patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…If these mismatch lesions were treated solely using angiography, as recommended by the German consensus group, all of them should be treated with stent implantation, since the residual DS was above 30%, even though the post-balloon FFR was > 0.75. Previous mid-and long-term follow-up studies in patients with an FFR after BA ≥ 0.75 showed comparable clinical outcomes between DCB and stent treatments [1,3,12]. Therefore, FFR-guided DCB treatment could safely reduce the number of unnecessary stent implantations in this mismatch population.…”
Section: Provisional Strategy Guided By Physiologymentioning
confidence: 86%
See 2 more Smart Citations
“…If these mismatch lesions were treated solely using angiography, as recommended by the German consensus group, all of them should be treated with stent implantation, since the residual DS was above 30%, even though the post-balloon FFR was > 0.75. Previous mid-and long-term follow-up studies in patients with an FFR after BA ≥ 0.75 showed comparable clinical outcomes between DCB and stent treatments [1,3,12]. Therefore, FFR-guided DCB treatment could safely reduce the number of unnecessary stent implantations in this mismatch population.…”
Section: Provisional Strategy Guided By Physiologymentioning
confidence: 86%
“…During the BA era, Bech et al [2] demonstrated that patients with a residual DS of  35% and an FFR value after BA of ≥ 0.90 had excellent clinical outcomes to 2-years. Further, in a previous study, it was demonstrated that DCB treatment after successful BA with a resultant FFR value ≥ 0.75 was safe and effective, without the additional risk of acute vessel closure [3].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent European data also showed that the FFR-guided DCB-only approach of de novo lesions (cutoff value of FFR: 0.80) was feasible and safe in stable CAD, showing positive remodeling without lumen loss by OCT at 6 months [40]. Another study showed that the safety and efficacy of DCB was comparable with DES when the cut-off value of FFR was 0.75 after balloon angioplasty [41]. Recent Chinese data showed that DCB for de novo coronary lesions with diameters greater than 2.8 mm was safe and effective as for small vessel lesions [42].…”
Section: De Novo Lesionmentioning
confidence: 97%
“…The purpose of the study by Her et al was to compare the efficacy of paclitaxel-coated balloon (PCB) treatment with stent implantation for de novo coronary lesions after successful plain old balloon angioplasty (POBA) guided by fractional flow reserve (FFR) [9]. 200 patients were included in the study and the primary endpoint was late lumen loss at 9 months.…”
Section: X-ray Imagingmentioning
confidence: 99%